Perceived Healthcare Service Quality and Brand Image on Patients' Loyalty in Zambia - Somaiya, Vimal (Digital Repository of Theses - SSBM Geneva, 2025)
The Zambian government encounters significant challenges in providing beneficial health care services to its citizens. Over the years, Zambia has implemented policies as part of an ambitious effort to decentralize the health system in order to solve this societal issue. The National Health Policy, in particular, aims to provide equitable access to high-quality, reasonably priced healthcare as close to the family as feasible. Consequently, the required actions are being taken to guarantee that Zambia's healthcare system is of higher quality. The purpose of this study is to ascertain how patient loyalty, brand image, and patient happiness are impacted by the quality of services provided at health institutions in Zambia. The research outcomes of this study give insights on how best the healthcare industry can be improved in order to ensure patient satisfaction and quality healthcare service. This study on healthcare service quality in Zambia focuses on important aspects influencing patient choice and satisfaction. The findings emphasize the importance of a patient-centered strategy that prioritizes not just clinical knowledge but also clear communication, polite interactions, and cultural sensitivity. A favorable brand reputation based on previous positive experiences emerged as a crucial criterion for patients, stressing the importance of healthcare facilities investing in building trust and consistently offering high-quality care. Findings reveal a strong correlation between healthcare service quality and the factors of patient satisfaction, brand image, and patient loyalty. Patients prioritize factors that contribute to a positive healthcare experience, including courteous and attentive medical personnel, efficient service delivery, effective treatment, a clean and hygienic environment, and access to modern technology. Using qualitative analyses, key issues affecting the provision of good healthcare in Zambia are identified in this study, including rising medical costs that burden patients and may delay or prevent them from seeking necessary care, and disparities in access, particularly in rural areas, which create geographic barriers to healthcare services. Also, this study recommends that successful training programs can enhance staff abilities in communication, service delivery, and treatment effectiveness. Building a patient-centered healthcare system in Zambia requires a focus on continuous improvement and frequent feedback. Policymakers can consider a multifaceted strategy to improve affordability, with public-private partnerships being particularly effective for funding critical infrastructure development projects, such as new clinics or upgraded communication networks in remote locations. However, the research reveals significant obstacles that keep Zambia's healthcare system from reaching its full potential. Rising medical costs, unequal access to care, and a scarcity of qualified personnel are all important barriers to providing equitable healthcare to all Zambians.